STRATIFIKASI SOSIAL DALAM NOVEL ORANG MISKIN DILARANG SEKOLAH KARYA WIWID PRASETYO - Ariesma Setyarum (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
The objective of the study is to reveal the social stratification in the novel Orang Miskin Dilarang Sekolah as well as its impacts.This research was literary research. It studied a literary work, Wiwid Prasetyo’s Orang Miskin Dilarang Sekolahnovel. The method of this research was literature research. The sociology of literature was used as the theory. This theory was used to reveal the social class in the novel Orang Miskin Dilarang Sekolah. The data include the texts in the novel which become the object of the study. This study is a literay study on the novel written by Wiwid Prasetyo and thus it employs the literary method. Based on the statement of problem, this research could be concluded that the social stratification in this novel were upper class, middle class and lower class.